2019
DOI: 10.18549/pharmpract.2019.3.1494
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications among the elderly in primary care in Thailand from three different sets of criteria

Abstract: Objective:The primary objective was to examine potentially inappropriate medications (or PIMs) in the elderly using three different criteria: Beers 2015, STOPP version 2, and Winit-Watjana (for Thai elderly patients). The secondary objective was to examine PIM-related factors.Methods:This is a retrospective cross-sectional study. Eligible patients were aged ≥65 years in a primary care unit. Demographic data, medical prescriptions in the past year, clinical data and diagnoses were collected from electronic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
5
21
2
1
Order By: Relevance
“…The previous study conducted in the same clinic 2 years ago reported 53.3% of polypharmacy and 59% of PIMs according to the Beers 2015 criteria. 9 Our current study found that the prevalence of polypharmacy and PIMs was still high, though it was lower than the previous study. The most PIMs prescribed for the patients were anticholinergics, omeprazole, and NSAIDs, which were different from the previous study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The previous study conducted in the same clinic 2 years ago reported 53.3% of polypharmacy and 59% of PIMs according to the Beers 2015 criteria. 9 Our current study found that the prevalence of polypharmacy and PIMs was still high, though it was lower than the previous study. The most PIMs prescribed for the patients were anticholinergics, omeprazole, and NSAIDs, which were different from the previous study.…”
Section: Discussioncontrasting
confidence: 70%
“… 7 In Thailand, orphenadrine, dimenhydrinate, and benzodiazepine are the most common PIMs prescribed according to the 2015 Beers criteria, while benzodiazepine and first-generation antihistamine were common in STOPPv2. 9 …”
Section: Introductionmentioning
confidence: 99%
“…International studies have shown prevalence rates of 43% in Canada [ 15 ], 42,7% in New Zealand [ 11 ], and 46.1% in Portugal [ 41 ]. In Asian countries, the prevalence was 12.7% in Oman [ 42 ], 34.0% in India [ 43 ], 39.4% in Indonesia [ 44 ], 53,1% in Kuwait [ 14 ], and 59.3% in Thailand [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Indeed, polypharmacy was a strong predictor for PIP in most published research worldwide. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%